THE JUSTIFICATION OF MATHEMATICAL MODEL FOR SINGULARLY FIXED CONSOLE - Irina Oblasova; Natalia Shiryaeva (Вестник Северо-Кавказского федерального университета, 2022)
The article is dedicated to mathematical model continuous one-dimensional elastic system of beam type- a consoles with irregular interaction with external ambience. Built integro- differential equation has a physical na-ture, arising from the problem of minimization of the energy functional for the console.